2021
DOI: 10.1007/jhep04(2021)143
|View full text |Cite
|
Sign up to set email alerts
|

Unitarity in KK-graviton production, a case study in warped extra-dimensions

Abstract: The Kaluza-Klein (KK) decomposition of higher-dimensional gravity gives rise to a tower of KK-gravitons in the effective four-dimensional (4D) theory. Such massive spin-2 fields are known to be connected with unitarity issues and easily lead to a breakdown of the effective theory well below the naive scale of the interaction. However, the breakdown of the effective 4D theory is expected to be controlled by the parameters of the 5D theory. Working in a simplified Randall-Sundrum model we study the matrix elemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…These clashing expectations can be resolved by realizing that the 4D theory that arises from the KK-decomposition of extra dimensions does not just contain a single spin-2 field but a tower of KK-gravitons and their interactions instead. We recently analyzed the high energy limit of KK-graviton production in warped extra-dimensions and found that the contribution of the other KK-gravitons conspire to cancel the contributions that grow faster than s 1 [18]. 2 Naturally, this will have an impact on the DM production rates and can change the amount of produced in the early Universe considerably.…”
Section: Jhep11(2021)036mentioning
confidence: 99%
See 4 more Smart Citations
“…These clashing expectations can be resolved by realizing that the 4D theory that arises from the KK-decomposition of extra dimensions does not just contain a single spin-2 field but a tower of KK-gravitons and their interactions instead. We recently analyzed the high energy limit of KK-graviton production in warped extra-dimensions and found that the contribution of the other KK-gravitons conspire to cancel the contributions that grow faster than s 1 [18]. 2 Naturally, this will have an impact on the DM production rates and can change the amount of produced in the early Universe considerably.…”
Section: Jhep11(2021)036mentioning
confidence: 99%
“…the 5D graviton, and a scalar perturbation r, the so-called radion. A detailed discussion of this expansion and the resulting Lagrangian up to third order in the fields can for example be found in [18,21]. Second, one utilizes a Kaluza-Klein decomposition of the 5D graviton…”
Section: Jhep11(2021)036mentioning
confidence: 99%
See 3 more Smart Citations